Влияние барических обработок на свойства структур Al - SiO –n-Si (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of influences of comprehensive hydrostatical compression on the closeness of the electronic state, non communicative on the interphase border of section of Si-SiO .